2012
DOI: 10.5923/j.ajps.20120204.02
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Properties of Egg Shell and Fish Bone Powder Filled Polypropylene

Abstract: The mechanical and end-use properties of egg shell and fish bone powder filled polypropylene have been determined at filler contents, 0 to 40 wt. %, and particle sizes, 0.150, 0.30, and 0.420 µm. Talc, of particle size, 0.150 µm was used as the reference filler. The incorporation of egg shell and fish bone powder into polypropylene resulted in improvement in the tensile strength, tensile modulus, flexural, and impact strength of the composites, and these properties increased with increase in filler contents, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 23 publications
3
16
0
2
Order By: Relevance
“…The impact strength of the composite increased with the increase in filler content as shown in Fig 15, while lower particle size favours impact strength. Such an increase in impact strength of a thermoplastic composite with an increase in filler content has been reported by Ahmed [10]; Bigg [12] in his study on "Mechanical Properties of Particulate filled Polymers and Igwe [13]. As the concentration of the filler content increased, Izod notched impact energy increased due to the more energy required for crack propagate [11].…”
Section: Analysis Of Response Surface:-supporting
confidence: 54%
“…The impact strength of the composite increased with the increase in filler content as shown in Fig 15, while lower particle size favours impact strength. Such an increase in impact strength of a thermoplastic composite with an increase in filler content has been reported by Ahmed [10]; Bigg [12] in his study on "Mechanical Properties of Particulate filled Polymers and Igwe [13]. As the concentration of the filler content increased, Izod notched impact energy increased due to the more energy required for crack propagate [11].…”
Section: Analysis Of Response Surface:-supporting
confidence: 54%
“…At 30 and 40 phr loading, ESP and ESP M fillers tends to form agglomerates which act as stress concentration point in the composites. Stress transfer between the matrix and filler will become less efficient and this reduces the strength . Agglomeration of ESP at higher bonding is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As reported earlier, the tensile modulus of HDPE/ESP M composites is higher compared to pure HDPE and also HDPE/ESP composites. Igwe and Onuegbu , Nwanonenyi and Chike‐Onyegbula , and Nwanonenyi et al reported that with addition of coupling agent, matrix and ESP adhere more and more stress is required for small deformation, hence high tensile modulus resulting in low elongation of break at high tensile strength.…”
Section: Resultsmentioning
confidence: 99%
“…Increment of tensile modulus due to demobilisation of polymeric chain on filler surface will cause decrement in ductility and elongation at break. Such a reduction in elongation at break of a polymer composite with increment of tensile modulus has been reported by Igwe and Onuegbu, Nwanonenyi and Chike-Onyegbula, and Nwanonenyi et al [19][20][21]…”
Section: Resultsmentioning
confidence: 53%